Abundant primary piRNAs, endo-siRNAs, and microRNAs in a Drosophila ovary cell line - Lau, Nelson C.; Robine, Nicolas; Martin, Raquel; Chung, Wei-Jen; Niki, Yuzo; Berezikov, Eugene; Lai, Eric C. (Genome Research, 2009)
Piwi proteins, a subclass of Argonaute-family proteins, carry ∼24–30-nt Piwi-interacting RNAs (piRNAs) that mediate gonadal defense against transposable elements (TEs). We analyzed the Drosophila ovary somatic sheet (OSS) cell line and found that it expresses miRNAs, endogenous small interfering RNAs (endo-siRNAs), and piRNAs in abundance. In contrast to intact gonads, which contain mixtures of germline and somatic cell types that express different Piwi-class proteins, OSS cells are a homogenous somatic cell population that expresses only PIWI and primary piRNAs. Detailed examination of its TE-derived piRNAs and endo-siRNAs revealed aspects of TE defense that do not rely upon ping-pong amplification. In particular, we provide evidence that a subset of piRNA master clusters, including flamenco, are specifically expressed in OSS and ovarian follicle cells. These data indicate that the restriction of certain TEs in somatic gonadal cells is largely mediated by a primary piRNA pathway.